REPRODUCTION AND LARVAL CULTURE OF THE BROWN CLOWNFISH (Premnas biaculeatus) UNDER CONTROLLED CONDITIONS - Luz Estela Rodríguez-Ibarra; Maria Isabel Abdo-de la Parra; Gabriela Velasco-Blanco; Juan Manuel Martinez-Brown (Tropical and Subtropical Agroecosystems)
Background: Interest in ornamental marine fish, especially species associated with coral reefs, is rapidly growing. Most of the fish traded come from the wild, and collection methods harm coral reefs and cause massive mortalities in non-target species. To make the activity sustainable, it is necessary to develop aquaculture biotechnologies to reduce the collection of wild organisms and lessen the pressure on their natural environment. Objective: To develop protocols for the reproduction and larval rearing of the maroon clownfish (Premnas biaculeatus) for the sustained production of juveniles in captivity. Methodology: Two pairs of P. biaculeatus were placed in two aquariums of a recirculating system with filtered seawater. The obtained eggs were incubated in 100 L tanks. The larvae were fed with rotifers Brachionus rotundiformis, Artemia sp. nauplii, and weaned onto a commercial diet. The larvae were measured at hatching and every four days until weaning. Results: The clownfish pairs began spawning 4-5 months after being placed in the recirculating system and continued spawning every 15-20 days. The eggs hatched 6-7 days after fertilization (DAF), and the hatched larvae measured 3.4±0.06 mm in total length (TL). At 19 days after hatching (DAH), after completing weaning, they measured between 9.8 to 11.5 mm in TL; at 26 DAH, they measured between 10.8 to 13.1 mm. After one month, between 800 to 1,000 juveniles were obtained for commercialization. Implications: The reproduction and larval rearing protocols of the maroon clownfish P. biaculeatus described in this work can be used to obtain juveniles in captivity for commercialization; additionally, they can serve as a basis for developing other protocols for obtaining juveniles of other ornamental marine fish species for commercialization, contributing to the protection of their natural environment. Conclusion: The results obtained demonstrated the viability of maintaining P. biaculeatus breeders in captivity and achieving their natural reproduction, larval rearing, and mass production of juveniles throughout the year.